Students’ perception about ChatGPT’s impact on their Academic Education - Silvestre, Ana Sofia Schweizer; Amaral, Elaina Lynn de Moura; Holanda, Maria Eduarda; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na Educação, 2023)
Goal: This study explores the impact of ChatGPT, an OpenAI language model, on undergraduate students in Brazil, aiming to uncover its benefits and challenges in higher education. It investigates students’ experiences and perceptions, providing insights for educators and policymakers in Brazil and beyond. Method: A survey of 206 undergraduate students was conducted to gather data on profiles, usage frequency, and perceptions of ChatGPT’s impact in education. Results: Participants recognized ChatGPT’s value in enhancing productivity, organization, study orientation, code writing, and text revision. Concerns were also raised about user dependency, answer reliability, and ethical considerations. Conclusions: Undergraduate students perceive ChatGPT positively, but are also mindful of its limitations and potential negative effects. Integrating it into education requires careful consideration and the promotion of responsible usage. Educating users on ethical guidelines and addressing concerns can maximize benefits and mitigate drawbacks. This research contributes to understanding the implications, applications, and challenges of incorporating ChatGPT into education, emphasizing the need for further research and a balanced approach.